Muscle density analysis in COVID-19 - Bozdag, Pinar Gundogan; Baykara, Murat; Taş, Nevsun Pıhtılı (My University, 2022)
Aim: Coronavirus-2019 (COVID-19) was declared a pandemic by the World Health Organization, continues to spread globally, and patients may not exhibit specific musculoskeletal involvement symptoms. Materials and Methods: Clinical data and images of 389 consecutive patients, who applied to the pandemic outpatient clinic with a COVID-19 pre-diagnosis with musculoskeletal complaints, and 203 consecutive control patients who underwent thoracic computed tomography (CT) for an unrelated reason and diagnosed as normal were included in the study. Bilateral sternocleidomastoid and trapezius muscle CT density and blood creatine kinase (CK) levels of all participants were obtained. Results: In COVID-19 patients, a significant decrease in sternocleidomastoid muscle density was observed when compared to radiological grade; however, a significant increase in the density of the trapezius muscle was identified. In CK values, there was a significant increase in trapezius density. Conclusion: Although the cause or effect was controversial, respiratory muscles were affected due to forced breathing and muscle damages were determined. This study demonstrated the need for multicenter studies with detailed neurological and electrophysiological tests and pathological correlations with an adequate number of patients.
Keywords: Genel ve Dahili Tıp; Patoloji; İmmünoloji